Copper Recovery of E-Waste Disposal (SIMCARD) by Using Electro-Generated Chlorine - Prasetyo Chandra; M. Maktum Muharja Al Fajri; Sri Rachmania Juliastuti (Journal of Fundamentals and Applications of Chemical Engineering, 2022)
One method for dissolving Cu from e-waste is to use electro-leaching. The waste used is Simcard and NaCl as electrolytes. Simcard contains copper metal and several other valuable metals such as silver (Ag), gold (Au) and palladium (Pa). The electro-leaching process is carried out in an electrolytic cell reactor where chlorine gas will be produced from the electrolysis process, then chlorine gas will extract the copper contained in the Simcard. This research was conducted by varying the electrode potential (voltage)/electric current (amperes), salt concentration and time. From this research, Simcard contains copper (Cu) by 40.53% and can be separated by electro-leaching method in a stirred acrylic reactor with the best results under operating conditions; a temperature of 30⁰ C, a pressure of 1 atm, a concentration of 10% salt solution, a potential difference of 10 Volts, a leaching time of 60 minutes, and a stirring speed of 600 rpm resulted in a Simcard metal alloy yield of 98.59%.